Molding material
A cellulose fiber and resin blend with controlled molecular weight distribution addresses thermal degradation issues in molding materials, ensuring robust mechanical properties despite thermal stress.
Patent Information
- Application Number
- JP2023107006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Conventional composite materials made from cellulose fibers and resins experience a decrease in mechanical strength due to thermal degradation during molding processes, particularly when products are melted and remolded.
A molding material comprising cellulose fibers and a resin blend of saturated aliphatic polyester and highly polar polyester, with specific molecular weight distribution characteristics, enhances mechanical strength by maintaining integrity under thermal stress.
The material maintains excellent mechanical properties, such as Charpy impact strength and flexural modulus, even after exposure to molding heat history, through the use of a resin with controlled molecular weight distribution and compatibility agents.
Smart Images

Figure 2025006299000001 
Figure 2025006299000002 
Figure 2025006299000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a molding material. [Background technology]
[0002] Conventionally, molding materials containing cellulose fibers, resin, etc. have been known. For example, Patent Document 1 discloses a composite material containing paper-derived fibers and biodegradable resin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2000-006142 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the mechanical strength of the composite materials of the prior art can be reduced if they have a thermal history of molding, for example, when a molded product or a gate material used during molding is melted, pelletized, and then molded again. [Means for solving the problem]
[0005] One aspect of the molding material according to the present invention is A molding material comprising cellulose fibers and a resin, The resin includes a saturated aliphatic polyester and a highly polar polyester, The resin has a molecular weight distribution curve by a GPC method, which has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 at a weight average molecular weight lower than the maximum value 2, The area value at the local maximum value 2 is smaller than the area value at the local maximum value 1. [Brief description of the drawings]
[0006] [Figure 1]FIG. 1 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 1). [Diagram 2] FIG. 2 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 2). [Diagram 3] FIG. 3 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, an embodiment of the present invention will be described. The embodiment described below is an example of the present invention. The present invention is not limited to the following embodiment, and includes various modified forms that are implemented within the scope that does not change the gist of the present invention. Note that not all of the configurations described below are necessarily essential configurations of the present invention.
[0008] 1.Molding material A molding material according to one embodiment of the present invention is a molding material comprising cellulose fibers and a resin, the resin comprising a saturated aliphatic polyester and a highly polar polyester, and in a molecular weight distribution curve measured by a GPC method, the resin has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 below the weight average molecular weight at maximum value 2, and the area value at maximum value 2 is smaller than the area value at maximum value 1.
[0009] Molding heat, such as when molding products or gate materials are melted and pelletized and then molded again If the resin in the molding material has a history, various properties will deteriorate due to thermal decomposition. Low-melting-temperature resins that melt at less than 200°C are particularly susceptible to thermal decomposition.
[0010] Therefore, the inventors conducted extensive research and found that when a resin contains an appropriate amount of high molecular weight components, the resin has excellent mechanical strength, such as Charpy impact strength and flexural modulus, even when the resin has a molding thermal history.
[0011] The molding material can be molded by known molding methods such as injection molding and press processing. Molded products made from the molding material are suitable as replacements for polystyrene and the like for various containers, sheets, and housings for office equipment such as printers and home appliances.
[0012] The various raw materials contained in the molding material will be described below.
[0013] 1.1 Cellulosic fibers The molding material according to the present embodiment contains cellulose fibers. The cellulose fibers function as a filler in the molded product, and contribute to increasing the bulk of the molding material and improving the physical properties, such as the strength, of the molded product.
[0014] Cellulose fibers are derived from plants and are relatively abundant natural materials. Therefore, the use of cellulose fibers promotes the reduction of environmental impact compared to the use of synthetic fibers. Cellulose fibers are also advantageous in terms of raw material procurement and cost. Furthermore, among various fibers, cellulose fibers have high theoretical strength, which contributes to improving the strength of molded products. In addition to using virgin pulp as cellulose fibers, waste paper, old cloth, etc. may be defibrated and reused.
[0015] The cellulose fibers are mainly made of cellulose, but may contain components other than cellulose, such as hemicellulose and lignin. The cellulose fibers may be subjected to a process such as bleaching.
[0016] From the viewpoint of improving the appearance of the surface of a molded article, the fiber length of the cellulose fibers is preferably less than 500 μm, and more preferably less than 50 μm. The fiber length of the cellulose fibers is determined by a method in accordance with ISO 16065-2:2007.
[0017] The content of cellulose fiber is preferably 9% by mass or more, more preferably 18% by mass or more, even more preferably 27% by mass or more, even more preferably 36% by mass or more, and particularly preferably 45% by mass or more, based on the total mass of the molding material. The content of cellulose fiber is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, based on the total mass of the molding material. When the content of cellulose fiber is within the above range, good mechanical strength tends to be obtained even when there is a molding heat history.
[0018] 1.2 Resin The molding material according to this embodiment contains a resin, and the resin includes a saturated aliphatic polyester and a highly polar polyester.
[0019] Saturated aliphatic polyesters act as a resin matrix, ensuring the impact resistance (toughness) of the molded body. However, they have low compatibility with cellulose fibers, and the two materials tend to peel off at the interface. Therefore, by using highly polar polyesters, they function as a compatible solvent between the cellulose fibers and the saturated aliphatic polyester, and can suppress the peeling at the interface.
[0020] The resin content is preferably equal to or less than the above-mentioned cellulose fiber content, in which case better mechanical strength tends to be obtained even in the case where there is a molding heat history.
[0021] 1.2.1 Saturated aliphatic polyesters The saturated aliphatic polyester has thermoplasticity, and when a molded article is produced from the molding material, it melts and bonds the cellulose fibers together. The saturated aliphatic polyester is responsible for the physical properties of the molded article together with the cellulose fibers. The saturated aliphatic polyester may have a linear or branched alkylene group, but is preferably a linear alkyl polyester having a linear alkylene group. Such linear alkyl polyesters have increased toughness due to the linear alkylene group, and tend to mainly improve the impact strength of the molded article.
[0022] The saturated aliphatic polyester preferably contains, as raw material monomers, an alkyl dicarboxylic acid having an alkylene group with 2 to 8 carbon atoms and an alkylene diol having an alkylene group with 2 to 8 carbon atoms, more preferably an alkyl dicarboxylic acid having an alkylene group with 2 to 5 carbon atoms and an alkylene diol having an alkylene group with 3 to 5 carbon atoms, and even more preferably an alkyl dicarboxylic acid having an alkylene group with 2 to 3 carbon atoms and an alkylene diol having an alkylene group with 3 to 4 carbon atoms. When the saturated aliphatic polyester contains the above raw material monomers, better mechanical strength tends to be obtained even when there is a molding heat history. The saturated aliphatic polyester is preferably produced by copolymerizing the above-mentioned two kinds of raw material monomers. The copolymerization can be carried out by a known synthesis method.
[0023] Examples of the alkyl dicarboxylic acid include linear saturated aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. It is preferable to use one or more of these for the synthesis of the saturated aliphatic polyester.
[0024] Examples of the alkylene diol include dihydric alcohols such as 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol. It is preferable to use one or more of these for the synthesis of saturated aliphatic polyesters. The above-mentioned two types of raw material monomers are relatively easy to obtain and can be applied to industrial or commercial applications.
[0025] The saturated aliphatic polyester preferably contains one or more of polybutylene succinate, polybutylene succinate adipate, and polyethylene diadipate. These saturated aliphatic polyesters are biodegradable, so they can reduce the environmental impact of molded products, and tend to provide better mechanical strength even when the product has a molding heat history.
[0026] The content of the saturated aliphatic polyester is preferably 9% by mass or more, more preferably 18% by mass or more, and even more preferably 27% by mass or more, based on the total mass of the molding material. The content of the saturated aliphatic polyester is preferably 50% by mass or less, more preferably 45% by mass or less, based on the total mass of the molding material. When the content of the saturated aliphatic polyester is within the above range, even if there is a molding heat history, better mechanical strength tends to be obtained.
[0027] In addition, it is preferable that the content of the saturated aliphatic polyester is greater than the content of the highly polar polyester described below, and the total content of the saturated aliphatic polyester and the highly polar polyester is equal to or less than the content of the cellulose fiber described above. In such a case, even if there is a molding heat history, better mechanical strength tends to be obtained.
[0028] In addition, when the content of the saturated aliphatic polyester is 100 parts by mass, the content of the highly polar polyester described below is 10 parts by mass or more and 70 parts by mass or less (preferably 10 parts by mass or more and 50 parts by mass or less, more preferably 10 parts by mass or more and 30 parts by mass or less), and the content of the above-mentioned cellulose fiber is preferably 110 parts by mass or more and 570 parts by mass or less (preferably 110 parts by mass or more and 300 parts by mass or less, more preferably 110 parts by mass or more and 200 parts by mass or less, and even more preferably 110 parts by mass or more and 150 parts by mass or less). In such a case, even if there is a molding heat history, better mechanical strength tends to be obtained.
[0029] 1.2.2 Highly polar polyester The highly polar polyester improves the compatibility between the cellulose fiber and the saturated aliphatic polyester, which increases the wettability of the saturated aliphatic polyester to the cellulose fiber, and mainly improves the bending strength of the molded product.
[0030] The highly polar polyester has a molecular structure with a relatively high polarity, and preferably has 1 or more oxygen atoms per 2 carbon atoms in the repeating structure derived from the raw material monomer. In such a case, even if there is a molding heat history, better mechanical strength tends to be obtained. In detail, the highly polar polyester preferably contains raw material monomers such as lactic acid, hydroxybutyric acid, oxysuccinic acid, citric acid, malonic acid, succinic acid, serine, threonine, acrylic acid, methyl acrylate, and vinylacetic acid as raw material monomers.
[0031] Specifically, the highly polar polyester preferably contains one or more of polylactic acid, polyhydroxybutyric acid, polyacrylic acid, polymethyl acrylate, and polyvinyl acetate. The highly polar polyester may also be a copolymer having a structure derived from lactic acid or acetic acid in its molecular structure, such as polyethylene succinic acid. Among these, the highly polar polyester preferably contains one or more of polylactic acid and polyhydroxybutyric acid. Such compounds are biodegradable and can reduce the environmental load, and tend to provide better mechanical strength even when there is a molding heat history.
[0032] The content of the highly polar polyester is preferably 2% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more, based on the total mass of the molding material. The content of the highly polar polyester is preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less, based on the total mass of the molding material. When the content of the highly polar polyester is within the above range, even if there is a molding heat history, better mechanical strength tends to be obtained.
[0033] 1.2.3 Other resins The resin contained in the molding material according to the present embodiment may contain a resin other than the saturated aliphatic polyester and the highly polar polyester. Examples of such a resin include olefin-based resins such as polyethylene and polypropylene, urethane-based resins, and acrylic-based resins.
[0034] 1.2.4 Molecular weight distribution The resin contained in the molding material according to this embodiment has, in a molecular weight distribution curve by GPC method, a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 below the weight average molecular weight at maximum value 2, and the area value at maximum value 2 is smaller than the area value at maximum value 1. In this way, by having the resin have an appropriate amount of high molecular weight components, it is possible to maintain mechanical strength even if thermal decomposition of the resin occurs due to the molding heat history.
[0035] The GPC method is a gel permeation chromatography method, for example, the following procedure. The measurement can be performed in the following order. A GPC device (ACQUITY APC, manufactured by Waters) with two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) connected in series is used as the measurement device. The measurement sample (molding material) is dissolved in chloroform as the eluent, filtered through a filter with a pore size of 0.45 μm, and the dissolved components are subjected to GPC analysis to obtain the molecular weight distribution curve of the resin. Here, the column temperature is set to 40°C, and an IR detector is used as the detector. Polystyrene (manufactured by Agilent) is used as the standard sample.
[0036] The peak calculation method can be, for example, as follows. The chromatogram is treated as a linear function, and the position where the slope becomes 0 when differentiated is taken as the peak top. The chromatogram is treated as a linear function, and the position where the slope becomes 0 when differentiated is taken as the peak boundary. The peak is divided vertically from the peak boundary position, and the area value of each peak is calculated. If the peaks are sufficiently separated, the area value may be treated as a single peak. If the two overlapping peaks can be sufficiently distinguished, they may be treated as a shoulder peak, and the base of the smaller peak may be drawn with a straight line to calculate the area value. Furthermore, the area of each peak may be calculated using peak separation software. However, the agreement rate must be 90% or more.
[0037] The resin contained in the molding material according to this embodiment has a maximum value 2 at a weight average molecular weight of 100,000 or more in a molecular weight distribution curve by GPC method, but the weight average molecular weight is preferably 110,000 or more, more preferably 120,000 or more, and even more preferably 130,000 or more. The maximum value 2 is preferably at a weight average molecular weight of 500,000 or less, more preferably 400,000 or less, and even more preferably 300,000 or less. If the maximum value 2 is within the above range, better mechanical strength tends to be obtained even in the case of a molding heat history.
[0038] The resin contained in the molding material according to this embodiment has a maximum value 1 in the molecular weight distribution curve by the GPC method, which is less than the weight average molecular weight at the maximum value 2, and the maximum value 1 is preferably at a weight average molecular weight of 150,000 or less, more preferably at 120,000 or less, and even more preferably at 100,000 or less. The maximum value 1 is preferably at a weight average molecular weight of 30,000 or more, more preferably at 50,000 or more, and particularly preferably at 60,000 or more. If the maximum value 1 is within the above range, better mechanical strength tends to be obtained even when there is a molding heat history.
[0039] Here, (weight average molecular weight at maximum value 2) / (weight average molecular weight at maximum value 1) is preferably more than 1.0 and not more than 5.0, more preferably 1.1 or more and not more than 4.0, even more preferably 1.2 or more and not more than 3.5, and particularly preferably 1.5 or more and not more than 3.0. In this case, even if there is a molding thermal history, better mechanical strength tends to be obtained.
[0040] 1.3 Crosslinking Agent The molding material according to the present embodiment may further contain a crosslinking agent. By containing a crosslinking agent, it is easy to adjust the molecular weight distribution of the resin, and therefore even if there is a molding heat history, better mechanical strength tends to be obtained.
[0041] The crosslinking agent is preferably one having a reactive group capable of crosslinking with polyester. More specifically, the crosslinking agent is preferably one having a reactive group selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic anhydride, and carboxylic acid. Crosslinking agents having such reactive groups can preferably react with saturated aliphatic polyesters and high polar polyesters, and are easy to adjust the molecular weight distribution in the resin, and thus tend to provide better mechanical strength even when there is a molding heat history.
[0042] The crosslinking agent may be a commercially available product, for example, Metablen P-1901 (Mitsubishi Chemical Corporation). Examples of suitable glyceryl ethers include glyceryl ethers, such as glyceryl ethers, glyceryl ethers, and glyceryl ethers are as follows: Deconal EX-321 (Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether), Deconal EX-211 (Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether), Duranate E402-B80B (Asahi Kasei Corporation, isocyanate), Carbodilite HMV-5CA-LC (Nisshinbo Chemical Inc.), Carbodilite Elastostab H01 (Nisshinbo Chemical Inc.), and Sigma-Aldrich: Product No. 188050 (Merck, poly(ethylene-alt-maleic anhydride)).
[0043] The content of the crosslinking agent is preferably 1% by mass or more, more preferably 2% by mass or more, based on the total mass of the molding material. The content of the crosslinking agent is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6% by mass or less, based on the total mass of the molding material. When the content of the crosslinking agent is within the above range, even if there is a molding heat history, better mechanical strength tends to be obtained.
[0044] The content of the crosslinking agent is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 15 parts by mass or less, and particularly preferably 7 parts by mass or more and 13 parts by mass or less, when the total content of the resins is taken as 100 parts by mass. When the content of the crosslinking agent is within the above range, better mechanical strength tends to be obtained even when there is a molding heat history.
[0045] 1.4 Flame retardants The molding material according to the present embodiment may contain a flame retardant. Known substances can be used as the flame retardant. Examples of the flame retardant include inorganic flame retardants such as antimony compounds, metal hydroxides, nitrogen compounds, and boron compounds, and organic flame retardants such as bromine compounds and phosphorus compounds.
[0046] As the flame retardant, commercially available products may be used, and examples thereof include Rabitol FP-110 (a phosphazene-based flame retardant manufactured by Mitsui Fine Chemicals, Inc.) and Exolit OP1230 (a phosphate-based flame retardant manufactured by Clariant).
[0047] The content of the flame retardant is preferably 5% by mass or more and 30% by mass or less, more preferably 8% by mass or more and 25% by mass or less, and even more preferably 10% by mass or more and 20% by mass or less, based on the total mass of the molding material. When the content of the flame retardant is within the above range, the flame retardancy of the molded product is improved, and better mechanical strength tends to be obtained even when the molded product has a molding heat history.
[0048] The content of the flame retardant is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 20 parts by mass or less, and even more preferably 10 parts by mass or more and 20 parts by mass or less, when the total content of the cellulose fiber, the saturated aliphatic polyester, and the high polarity polyester is taken as 100 parts by mass. When the content of the flame retardant is within the above range, the flame retardancy of the molded article is improved, and even if the molded article has a thermal molding history, better mechanical strength tends to be obtained.
[0049] 1.5 Other ingredients The molding material according to this embodiment may contain other components, such as a colorant, an insect repellent, an anti-fungal agent, an antioxidant, an ultraviolet absorbing agent, an aggregation inhibitor, and a mold release agent.
[0050] 2. Manufacturing method of molding material
[0051] A method for producing the molding material will now be described. A known method can be applied to produce the molding material. Specifically, for example, the method described below can be applied.
[0052] First, the above-mentioned raw materials are mixed in a single-shaft or twin-shaft mixer to form a strand shape. Next, the mixture is pelletized to produce pellet-shaped molding material.
[0053] The following method may also be used as a manufacturing method for the molding material. First, waste paper or pulp material is roughly crushed in a shredder device to produce cellulose fibers. Then, the cellulose fibers, saturated aliphatic polyester, high polarity polyester, and optionally a crosslinking agent are weighed and kneaded. Next, the kneaded raw materials are deposited in air to produce a sheet-like deposit. Since the deposit contains a lot of air and has a low density, it is compressed in a calendar device to remove the air and increase the density. Next, the deposit is heated in a non-contact manner using a heating furnace, and then hot-pressed in a heat press device.
[0054] In the heating furnace and heat press device, it is preferable to heat at a temperature about 20° C. higher than the melting temperature of the saturated aliphatic polyester and the highly polar polyester, which tends to form a sheet in which the raw materials are dispersed with less unevenness.
[0055] Next, the sheet is cut into a desired shape by a shredder device to obtain a pellet-shaped molding material. The desired shape of the molding material is not particularly limited, but is generally a cube of 2 mm 3 to 5 mm 3. The molding material can be manufactured by the above method. Note that the manufacturing method of the molding material is not limited to the above.
[0056] 3. Working Example The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0057] 3.1 Preparation of molding materials and test specimens Figures 1 to 3 (Tables 1 to 3) show the raw material compositions, molding methods, and evaluation results of molded products for the molding materials of each Example and Comparative Example. In the composition columns of Figures 1 to 3 (Tables 1 to 3), the units of values are parts by mass, and columns with no values indicate that the component is not contained.
[0058] The descriptions in Figures 1 to 3 (Tables 1 to 3) are supplemented as follows. <Saturated aliphatic polyester> Polybutylene succinate (product name Bio PBS FZ71PB, Mitsubishi Chemical Corporation) Polybutylene succinate adipate (product name BioPBS FD92PB, Mitsubishi Chemical Corporation) <Highly polar polyester> Polylactic acid (Terramac (registered trademark) TE-2000, Unitika Co., Ltd.) <Cellulose fiber> Product name: Guaiba BEKP, CMPC <Crosslinking Agent> Crosslinking agent 1 (Metabrene P-1901, manufactured by Mitsubishi Chemical Corporation) Crosslinking agent 2 (Deconal EX-321, Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether) Crosslinking agent 3 (Deconal EX-211, manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether) Crosslinking agent 4 (Duranate E402-B80B, Asahi Kasei Corporation, isocyanate) Crosslinking agent 5 (Carbodilite HMV-5CA-LC, Nisshinbo Chemical Inc.) Crosslinking agent 6 (Carbodilite Elastostab H01, Nisshinbo Chemical Co., Ltd.) Crosslinker 7 (Sigma-Aldrich: product no. 188050, Merck, poly(ethylene-alt-maleic anhydride) <Flame retardants> Flame retardant 1 (Lavitol FP-110, manufactured by Mitsui Fine Chemicals, Inc., a phosphazene-based flame retardant) Flame retardant 2 (Exolit OP1230, Clariant, phosphate ester flame retardant)
[0059] According to the compositions in Figures 1 to 3 (Tables 1 to 3), molding materials of Examples and Comparative Examples were manufactured. Specifically, saturated aliphatic polyester, highly polar polyester, cellulose fiber, etc. were weighed and fed into a Technovel twin-screw kneader KZW15TW-45MG for kneading. The kneading conditions were a maximum heating temperature of 180°C and an extrusion discharge rate of 1 kg / hr. Next, the material was processed into a strand shape and then pelletized into molding material in a pelletizer.
[0060] The weight average molecular weight of the molding material obtained above was measured by the GPC method. Specifically, a GPC device (ACQUITY APC, manufactured by Waters) with two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) connected in series was used as the measuring device. The measurement sample (molding material) was dissolved in chloroform as an eluent, filtered through a filter with a pore size of 0.45 μm, and the dissolved components were subjected to GPC analysis to obtain a molecular weight distribution curve of the resin. Here, the column temperature was set to 40° C., an IR detector was used as the detector, and polystyrene (manufactured by Agilent) was used as the standard sample. The peak calculation method was performed as described above.
[0061] The molding materials of each Example and Comparative Example were used to perform molding by injection molding or press processing. Specifically, the heating temperature of the molding material was 200°C for both injection molding and press processing. The injection molding device used was Nissei Plastic Industrial Co., Ltd.'s THX40-5V, and the press processing device used was Towa Seiki Co., Ltd.'s hydraulic press PHKS-40ABS.
[0062] Here, in the molding history of Figures 1 to 3 (Tables 1 to 3), "repellent once" means that the above-mentioned molding process was re-pelletized and molding was carried out again in the same manner as above, and "first time" means that molding was carried out only once without re-pelletization. Also, in the crosslinking agent addition step of Figures 1 to 3 (Tables 1 to 3), "at the time of repellent" means that the above-mentioned molding process was added when the material was re-pelletized, and "first time" means that the material was added only when the raw materials were mixed. In this manner, test pieces in each of the examples and comparative examples were obtained.
[0063] 3.2 Evaluation Test Charpy impact strength was used as an index of impact strength, and the test method was carried out in accordance with ISO 179 (JIS K7111). The shape of the test piece was a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 4.0 mm ± 0.2 mm, and a thickness of 10.0 mm ± 0.2 mm. The test device used was an Impact Tester IT manufactured by Toyo Seiki Seisakusho. In the Charpy impact test, the hammer weight was 4J (WR 2.14 N / m), the lifting angle was 150°, the notch remaining width was 8.0 mm ± 0.2 mm, and the notch angle was 45°.
[0064] The bending properties were used as an index of bending strength, and the test method was carried out in accordance with ISO 178 (JIS K7171). The shape of the test piece was a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 10.0 mm ± 0.2 mm, and a thickness of 4.0 mm ± 0.2 mm. The test equipment used was an Instron 68TM-30, and the test was carried out with a support distance of 64 mm.
[0065] For each level of test result obtained, the strength of the molded product was judged according to the following criteria. (Judgment criteria) A: Charpy impact strength is 7kJ / m 2 and flexural modulus is 4000MPa or more be. B: Charpy impact strength is 4kJ / m 2 or higher, and the flexural modulus is 4000 MPa or higher (excluding the range of A rating). C: Charpy impact strength is 4kJ / m 2 or higher, or the flexural modulus is 4000 MPa or higher (excluding the ranges of A and B). D: Charpy impact strength is 4kJ / m 2 and the flexural modulus is 4000 MPa or less (excluding the ranges of B and C). E: Not moldable.
[0066] 3.3 Evaluation results The evaluation results are shown in Figures 1 to 3 (Tables 1 to 3).
[0067] From the results shown in Figures 1 to 3 (Tables 1 to 3), it was found that the molding materials of each example, which contain cellulose fibers and a resin, where the resin contains a saturated aliphatic polyester and a highly polar polyester, and in a molecular weight distribution curve measured by GPC method, the resin has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 below the weight average molecular weight at maximum value 2, and the area value at maximum value 2 is smaller than the area value at maximum value 1, can obtain good mechanical strength even when they have a molding thermal history.
[0068] In contrast, the molding materials according to the comparative examples not satisfying the above-mentioned configuration did not provide good mechanical strength when subjected to a molding thermal history.
[0069] The following can be derived from the above-described embodiment.
[0070] One embodiment of the molding material is A molding material comprising cellulose fibers and a resin, The resin includes a saturated aliphatic polyester and a highly polar polyester, The resin has a molecular weight distribution curve by a GPC method, which has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 at a weight average molecular weight lower than the maximum value 2, The area value at the local maximum value 2 is smaller than the area value at the local maximum value 1.
[0071] In one embodiment of the molding material, The molding material may further contain a crosslinking agent.
[0072] In any one of the embodiments of the molding material, The crosslinker may have reactive groups selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic acid anhydride, carboxylic acid.
[0073] In any one of the embodiments of the molding material, the content of the saturated aliphatic polyester is greater than the content of the highly polar polyester, The total content of the saturated aliphatic polyester and the highly polar polyester may be equal to or less than the content of the cellulose fibers.
[0074] In any one of the embodiments of the molding material, When the content of the saturated aliphatic polyester is 100 parts by mass, The content of the highly polar polyester is 10 parts by mass or more and 70 parts by mass or less, The amount of the cellulose fibers may be 110 parts by mass or more and 570 parts by mass or less.
[0075] In any one of the embodiments of the molding material, The saturated aliphatic polyester may contain, as raw material monomers, an alkyldicarboxylic acid having an alkylene group with 2 or more and 8 or less carbon atoms, and an alkylene diol having an alkylene group with 2 or more and 8 or less carbon atoms.
[0076] In any one of the embodiments of the molding material, The saturated aliphatic polyester may include one or more of polybutylene succinate, polybutylene succinate adipate, and polyethylene adipate.
[0077] In any one of the embodiments of the molding material, The highly polar polyester may have a repeating unit derived from the raw material monomer in which the number of oxygen atoms is 1 or more per 2 carbon atoms.
[0078] In any one of the embodiments of the molding material, The highly polar polyester may include one or more of polylactic acid and polyhydroxybutyric acid.
[0079] In any one of the embodiments of the molding material, The cellulose fibers may have a fiber length of less than 500 μm.
[0080] In any one of the embodiments of the molding material, Contains flame retardants, The content of the flame retardant may be 1 part by mass or more and 20 parts by mass or less, when the total content of the saturated aliphatic polyester, the highly polar polyester, and the cellulose fibers is 100 parts by mass.
[0081] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the present invention includes a configuration that is substantially the same as the configuration described in the embodiment, for example, a configuration that has the same function, method, and result, or a configuration that has the same purpose and effect. The present invention also includes a configuration in which non-essential parts of the configuration described in the embodiment are replaced. The present invention also includes a configuration that has the same action and effect as the configuration described in the embodiment, or a configuration that can achieve the same purpose. The present invention also includes a configuration in which publicly known technology is added to the configuration described in the embodiment.
Claims
1. A molding material comprising cellulose fibers and a resin, The resin includes a saturated aliphatic polyester and a highly polar polyester, The resin has a molecular weight distribution curve by a GPC method, which has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 at a weight average molecular weight lower than the maximum value 2, A molding material, wherein the area value at the maximum value 2 is smaller than the area value at the maximum value 1.
2. The molding material according to claim 1 , further comprising a crosslinking agent.
3. 3. The molding material of claim 2, wherein the crosslinker has reactive groups selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic acid anhydride, and carboxylic acid.
4. the content of the saturated aliphatic polyester is greater than the content of the highly polar polyester, The molding material according to claim 1 or 2, wherein a total content of the saturated aliphatic polyester and the highly polar polyester is equal to or less than a content of the cellulose fiber.
5. When the content of the saturated aliphatic polyester is 100 parts by mass, The content of the highly polar polyester is 10 parts by mass or more and 70 parts by mass or less, The molding material according to claim 1 or 2, wherein the content of the cellulose fibers is 110 parts by mass or more and 570 parts by mass or less.
6. The molding material according to claim 1 or 2, wherein the saturated aliphatic polyester contains, as raw material monomers, an alkyl dicarboxylic acid having an alkylene group with 2 to 8 carbon atoms and an alkylene diol having an alkylene group with 2 to 8 carbon atoms.
7. 3. The molding material of claim 1 or 2, wherein the saturated aliphatic polyester comprises one or more of polybutylene succinate, polybutylene succinate adipate, and polyethylene adipate.
8. The molding material according to claim 1 or 2, wherein the highly polar polyester has a repeating unit derived from a raw material monomer in which the number of oxygen atoms is 1 or more relative to the number of carbon atoms of 2.
9. The molding material according to claim 1 or 2, wherein the highly polar polyester comprises one or more of polylactic acid and polyhydroxybutyric acid.
10. The molding material according to claim 1 or 2, wherein the cellulose fibers have a fiber length of less than 500 μm.
11. Contains flame retardants, 3. The molding material according to claim 1, wherein the content of the flame retardant is 1 part by mass or more and 20 parts by mass or less when the total content of the saturated aliphatic polyester, the highly polar polyester, and the cellulose fiber is 100 parts by mass.
Citation Information
Patent Citations
Composite material composed of paper and biodegradable resin, and its manufacture
JP2000006142A